Intelligent Human Computer Interaction 9th International Conference, IHCI 2017, Evry, France, December 11-13, 2017, Proceedings - Horain, Patrick; Achard, Catherine; Mallem, Malik; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY license.
Can Machines Design? Optimizing User Interfaces for Human Performance -- Geometrical Shapes Rendering on a Dot-Matrix Display -- Dynamic Hand Gesture Recognition for Mobile Systems Using Deep LSTM -- Adjustable Autonomy for UAV Supervision Applications Through Mental Workload Assessment Techniques -- Classification of Motor Imagery Based EEG Signals Using Sparsity Approach -- Mental Workload Assessment for UAV Traffic Control Using Consumer-Grade BCI Equipment -- Improving Classification Performance by Combining Feature Vectors with A Boosting Approach for Brain Computer Interface (BCI) -- List Navigation Using Edge Menu -- Simplexity and Vicariance. On Human Cognition Principles for Man-Machine Interaction -- Design Considerations for Self-paced Interactive Notes on Video Lectures - A Learner's Perspective and Enhancements of Learning Outcome -- Using Psycholinguistic Features for the Classification of Comprehenders from Summary Speech Transcripts -- Lector: Towards Reengaging Students in theEducational Process Inside Smart Classrooms -- Predicting Driver's Work Performance in Driving Simulator Based on Physiological Indices -- Interpersonal Human-Human and Human-Robot Interactions -- Exploring the Dynamics of Relationships Between Expressed and Experienced Emotions -- Standard Co-training in Multiword Expression Detection -- Comparative Study on Normalization in Emotion Recognition from Speech -- Detecting Vigilance in People Performing Continual Monitoring Task.
Keywords: Artificial intelligence; User interfaces (Computer systems).; Human-computer interaction; Database management; Computers, Special purpose; Artificial Intelligence; User Interfaces and Human Computer Interaction; Database Management; Special Purpose and Application-Based Systems